Efektivitas Pembelajaran Cooperative Script, Artikulasi dan Cooperative Integrated Reading and Composition terhadap Pemahaman Konsep Siswa Sekolah Dasar - Fitriyani, Yani; Gunawan, Agus; Lestari, Myrna Apriany (Profesi Pendidikan Dasar, 2020)
This study aims to determine the effectiveness of Cooperative Script (CS), Artikulasi, and Cooperative Integrated Reading and Composition (CIRC) learning model on understanding the concepts of elementary school students. This study used a quasi-experimental research method with Counterbalance design. This study used sample of 5th grade students in three elementary schools withÂ  total 75 students. The schools are SDN Pakembangan, SDN Kutakembaran 1, and SDN Kutakembaran 2. The instruments used included a concept understanding test, observation sheets, and documentation. Data analysis used was statistical testing with independent t-test which was previously tested for normality, homogeneity, and two mean difference at a significant level of 0.05. The results showed that the understanding of the concept of students who took learning with CS was better than students who took Artikulasi and CIRC. It was reviewed based on the student average score in the study I was 75.0, study II was 75.2 and 76.8 in the study III. The results of the two-difference test mean in study I, II, and III of the CS model obtained a significant value (2-tailed) 0.000 0.05. It means that there is a significant difference between the use of CS, Artikulasi, and CIRC models. Most of the students showed a positive attitude towards learning with CSÂ  model. Based on the findings, social studies learning with CS model can be used as an alternative learning model to improve the concept understanding of elementary students .